Cardiometabolic and immune response to exercise training in patients with metabolic syndrome: retrospective analysis of two randomized clinical trials - Lechner, Katharina; Kia, Sylvia; von Korn, Pia; Dinges, Sophia M.; Mueller, Stephan; Tjønna, Arnt-Erik; Wisløff, Ulrik; Van Craenenbroeck, Emeline M.; Pieske, Burkert; Adams, Volker; Pressler, Axel; Landmesser, Ulf; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Metabolic syndrome (MetS) is defined by the presence of central obesity plus ≥ two metabolic/cardiovascular risk factors (RF), with inflammation being a major disease-driving mechanism. Structured endurance exercise training (ET) may positively affect these traits, as well as cardiorespiratory fitness (V ̇O2peak).Aims: We explore individual ET-mediated improvements of MetS-associated RF in relation to improvements in V ̇O2peak and inflammatory profile.Methods: MetS patients from two randomized controlled trials, ExMET (n=24) and OptimEx (n=34), had performed four-or three-months supervised ET programs according to the respective trial protocol.V ̇O2peak, MetS-defining RFs (both RCTs), broad blood leukocyte profile, cytokines and plasma proteins (ExMET only) were assessed at baseline and follow-up. Intra-individual changes in RFs were analysed for both trials separately using non-parametric approaches. Associations between changes in each RF over the exercise period (n-fold of baseline values) were correlated using a non-parametrical approach (Spearman). RF clustering was explored by uniform manifold approximation and projection (UMAP) and changes in RF depending on other RF or exercise parameters were explored by recursive partitioning.Results: Four months of ET reduced circulating leukocyte counts (63.5% of baseline, P=8.0e-6), especially effector subtypes. ET response of MetS-associated RFs differed depending on patients´ individual RF constellation, but was not associated with individual change in V ̇O2peak. Blood pressure lowering depended on cumulative exercise duration (ExMET: ≥102 minutes per week; OptimEx-MetS: ≥ 38 minutes per session) and baseline triglyceride levels (ExMET: <150 mg/dL; OptimEx-MetS: <174.8mg/dL). Neuropilin-1 plasma levels were inversely associated with fasting plasma triglycerides (R: -0.4, P=0.004) and changes of both parameters during the ET phase were inversely correlated (R: -0.7, P=0.0001).Conclusions: ET significantly lowered effector leukocyte blood counts. The improvement of MetSassociated cardiovascular RFs depended on individual basal RF profile and exercise duration but was not associated with exercise-mediated increase in V ̇O2peak. Neuropilin-1 may be linked to exercisemediated triglyceride lowering.